Usability Strategic Evaluation on Innovative Teaching Material: InRA - Tukimin, Rozaini; Nik Yusoff, Nik Mohd Rahimi; Baharudin, Harun (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to explore the potential application of teaching aid in reading 29 Arabic letters with Fatha vowel using mental imagery techniques. This material is called InRA-Imagine and Read Arabic was developed using computer graphic software which contains picture icons resembling the writing forms of each Arabic Hijaiyyah Letters. A total of 70 teachers in primary schools were involved in testing the material. This study uses descriptive statistics (frequency, percentage and mean) to measure users’ perception of application usability. The findings showed that the application was at a high-usability level and the functioning aspect also did meet the users’ needs. In conclusion, this teaching aid has a great potential to be used in the Arabic Education subject as an alternative method to overcome the problem of reading Arabic Hijaiyyah letter.